DHTKD1 and OGDH display substrate overlap in cultured cells and form a hybrid 2-oxo acid dehydrogenase complex in vivo. (11th March 2020) - Leandro, João; Dodatko, Tetyana; Aten, Jan; Nemeria, Natalia S; Zhang, Xu; Jordan, Frank; Hendrickson, Ronald C; Sanchez, Roberto; Yu, Chunli; DeVita, Robert J; Houten, Sander M
Abstract: Glutaric aciduria type 1 (GA1) is an inborn error of lysine degradation characterized by a specific encephalopathy that is caused by toxic accumulation of lysine degradation intermediates. Substrate reduction through inhibition of DHTKD1, an enzyme upstream of the defective glutaryl-CoA dehydrogenase, has been investigated as a potential therapy, but revealed the existence of an alternative enzymatic source of glutaryl-CoA. Here, we show that loss of DHTKD1 in glutaryl-CoA dehydrogenase-deficient HEK-293 cells leads to a 2-fold decrease in the established GA1 clinical biomarker glutarylcarnitine and demonstrate that oxoglutarate dehydrogenase (OGDH) is responsible for this remaining glutarylcarnitine production. We furthermore show that DHTKD1 interacts with OGDH, dihydrolipoyl succinyltransferase and dihydrolipoamide dehydrogenase to form a hybrid 2-oxoglutaric and 2-oxoadipic acid dehydrogenase complex. In summary, 2-oxoadipic acid is a substrate for DHTKD1, but also for OGDH in a cell model system. The classical 2-oxoglutaric dehydrogenase complex can exist as a previously undiscovered hybrid containing DHTKD1 displaying improved kinetics towards 2-oxoadipic acid.